From post-industrial to post-modern society : new theories of the contemporary world - Krishan Kumar (Blackwell Publishers, 1995)
In the second edition of this classic study, Krishan Kumar introduces and assesses the rival claims of three theories crucial to an understanding of contemporary social theory: the information society; post-Fordism; and post-modernism. Explaining how these theories developed and why they have held such an appeal, the author provides the most readable and evenly-balanced account of three very different, but overlapping paradigms. In a new and substantial introduction, Kumar places the three key approaches within the context of contemporary discourse on globalization. From Post-Industrial to Post-Modern Society is essential reading for anyone seeking to understand contemporary theories of social, cultural, and economic change.